High cortical delta power correlates with aggravated allodynia by activating anterior cingulate cortex GABAergic neurons in neuropathic pain mice. Issue 2 (February 2020) - Li, Ya-Dong; Ge, Jing; Luo, Yan-Jia; Xu, Wei; Wang, Juan; Lazarus, Michael; Hong, Zong-Yuan; Qu, Wei-Min; Huang, Zhi-Li
Abstract : Abstract: Patients with chronic pain often report being sensitive to pain at night before falling asleep, a time when the synchronization of cortical activity is initiated. However, how cortical activity relates to pain sensitivity is still unclear. Because sleep is characterized by enhanced cortical delta power, we hypothesized that enhanced cortical delta power may be an indicator of intensified pain. To test this hypothesis, we used pain thresholds tests, EEG/electromyogram recordings, c-Fos staining, and chemogenetic and pharmacological techniques in mice. We found that sleep deprivation or pharmacologic enhancement of EEG delta power by reserpine and scopolamine dramatically decreased mechanical pain thresholds, but not thermal withdrawal latency, in a partial sciatic nerve ligation model of neuropathic pain mice. On the contrary, suppression of EEG delta power using a wake-promoting agent modafinil significantly attenuated mechanical allodynia. Moreover, when EEG delta power was enhanced, c-Fos expression decreased in most regions of the cortex, except the anterior cingulate cortex (ACC), where c-Fos was increased in the somatostatin- and parvalbumin-positive GABAergic neurons. Chemogenetic activation of GABAergic neurons in ACC enhanced EEG delta power and lowered mechanical pain thresholds simultaneously in naive mice. However, chemogenetic inhibition of ACC GABAergic neurons could not block mechanical allodynia. These results provided compelling evidence that elevated EEG delta power is accompanied with aggravated neuropathic pain, whereas decreased delta power attenuated it, suggesting that enhanced delta power can be a specific marker of rising chronic neuropathic pain and that wake-promoting compounds could be used as analgesics in the clinic. Abstract : Supplemental Digital Content is Available in the Text.Enhanced cortical EEG delta power is a remarkable indicator of high mechanical pain sensitivity.